Nature conservation versus flood protection: Participatory conflict resolution for the Białka River Valley - Anna Dubel; Karolina Królikowska (Economic and Environmental Studies (E&ES), 2014)
Białka River, the right tributary of the Vistula River, flowing in the mountainous Małopolska region is commonly referred to as one of the last non-modified streams in the Polish Carpathians. Most of the river valley is protected within PLH120024 Białka River Valley Natura 2000 site. However, there are also economic activities going on in the valley. Therefore the protection of assets (e.g. infrastructure, forests) against flood is desired by the local communities. Nature protection within this Natura 2000 site stands sometimes in conflict with flood protection actions preferred by the local communities. This kind of situation was observed at the beginning of the development of a management plan for this Natura 2000 site. In order to ease the tension and prevent conflicts between authorities and local community, which could hinder effective creation of the management plan, the participatory process was designed and conducted as an additional support for the standard management plan development meetings. The aim of the paper is to present the management experiment - especially designed and structured participatory process, supported by the observations and questionnaires, leading to the proposals of the win-win solutions for the Białka River Valley. The outcomes are reviewed with regard to the possibility of the process replication in other places. The key factors that enabled achievement of win-win solutions are discussed.
Keywords: 330; ecological conflict; participatory management; win-win solution; flood protection; Natura 2000; management plan